THE IMPACT OF HYBRID ELT ON EFL TEACHERS AND STUDENTS AT SECONDARY SCHOOLS DURING THE COVID 19 PANDEMIC - Romdhani, Moch Syahri; Aisyah, Siti (Universitas Muhammadiyah Metro, 2023)
The COVID-19 pandemic outbreak contrived change in various sectors, forcing the education sector to adjust and modify the daily conduct of teaching and learning in schools. This research highlights modifications done by schools as they have applied Hybrid Learning (HL) as an adjustment in the learning-teaching process. This study asked EFL Teachers and Students from thirty different schools in Surabaya and Sidoarjo in English Foreign Language (EFL) classes to complete the survey about how Hybrid Learning is implemented in their classes. This research analyzed the responses by using the descriptive design. Teachers' and students' responses about the changes in teaching instruments they used, school facilities to support their classes, period of adjustments, and their preference to choose either HL EFL to compare to conventional EFL class is collected through a survey. Their result shows that 1) Adjustments require a short period for students and teachers. 2) School facilities to support EFL HL classes. The study implies that conducting HL in emergencies requires adjustments. Thus, sufficient preparation from authorities is needed.